Accounting for commodity carbon footprints at the sub-national level: A case study of soybean exports from Brazil to China - Yuning Gao; Tao Zhang; Shantong Li; David Cleary (World Development Sustainability, 2025)
Quantifying the carbon footprint of agricultural products is crucial for effective carbon mitigation and responsible sourcing, given that the food production system accounts for approximately one-third of global carbon emissions. While country- and sector-specific carbon accounting offers broad insights, its sectoral aggregation limits actionable strategies for inclusive and sustainable supply chain governance. This study combines input-output data with high-resolution global soybean supply chain data at the sub-national level to quantify the embodied carbon in soybean exports from Brazilian states to China. The results reveal that the annual fossil fuel-related carbon footprint of exported soybeans surged from 7.2 million tons in 2014 to 18.5 million tons in 2018. Incorporating land-use change emissions amplifies the cumulative five-year footprint by an additional 17.6 million tons. At the sub-national level, Mato Grosso, Rio Grande do Sul, and Paraná are identified as the largest carbon exporters to China. Sourcing soybeans from Brazil’s central and southern regions, where soybean-related deforestation remains comparatively limited, emerges as a potential pathway toward more sustainable supply chain management. Finally, we examine uncertainties arising from comparisons with life cycle assessments, attributing discrepancies primarily to differences in accounting scope and margin allocations.